Building a Literacy Culture Based on Local Wisdom through Women's Leadership - Hasan Baharun; Abd Hamid Wahid; Khodijatul Qodriyah; Sri Wahyuni; Fatmawati Fatmawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The participation of women's leadership in early childhood education institutions can provide comfort and effectiveness in learning. Women who incidentally are quickly close to early childhood with maternal characteristics can understand the needs of early childhood. This study aims to analyze and understand women's leadership in building a literacy culture based on local wisdom in TK Azzainiyah Paiton Probolinggo. This study uses a phenomenological type of qualitative approach. The results showed that, firstly, leadership at Azzainiyah Kindergarten in Paiton Probolinggo involved women leaders who were highly dedicated to creating a literacy culture program based on local wisdom. Second, implementing a literacy culture based on local understanding through curriculum modification, literacy monitoring, strengthening human resources, knowledge sharing, and evaluation. The results of this study have implications for the importance of enhancing literacy in schools through strengthening local culture by leaders.